Photography technique as a medium to present floral motif in Islamic art / Shafirah Shaari … [et al.] - Shaari, Shafirah; Abdul Samat, Raziq; Wan Mohd Zain, Wan Nor Ayuni; Mohd Sharif, Nadzri; Meor Hamzah, Meor Hasmadi (Division of Research and Industry Linkages, 2017)
Islamic Art always describe as a components from Arabic calligraphy, geometrical pattern and arabesque (floral and vegetal motifs). The decoration or patterns usually represent illustration abstract rather than realistic. Photography is one of the medium that can be use to transform the Islamic art from illustration to realistic image. Before this, when talking about Islamic art in photography people will automatically remember about the image of mosque or Muslim only rather than nature or floral motif. For this research, we will use photography technique for studying floral motif in conveying the message of Islamic art. The purpose of this study is to (1) study the floral motif by using photography technique, (2) produce Islamic art in a new pattern. The method used in this study is start from observation as a field of study, pilot test for the experimental new pattern and distributing the questionnaire to get the data. Findings show photography play an important role in conveying the message of Islamic art to the audience. Each of flora motifs has their own aesthetic values, which can become new identity of pattern based on regional, This technique can become a new approach of Islamic art especially in a digital era.